Fabrication And Mass Attenuation Coefficient Of Bioplastic Rhizophora Spp. Particleboard - Ghasemi, Leila (2013)
Bioplastic Rhizophora spp. particleboard was fabricated with different treatment levels of 6%, 8% and 10% from polylactic acid (PLA) resin with target density 1 g/cmP3P. Particleboards produced were tested for the physical and mechanical properties. The surface morphology of the manufactured particleboard was viewed using Field Emission Scanning Electron Microcopy (FESEM). The results showed that samples produced from Rhizophora spp. at 8% and 10 % treatment level of PLA resin exhibited the highest internal bond (IB) strength and met Japanese Industrial Standards (JIS A-5908), while the 6% PLA sample did not fulfill the standard. In terms of physical characteristics water absorption (WA) and thickness swelling (TS), particleboard of 6%, 8 % and 10 % of PLA resin met the standard. The mass attenuation coefficients of the fabricated particleboards were determined by using X-ray fluorescence (XRF) emanating from pure metal plates. Materials used for the experimental set up were an Am-241 (P241PAm) source with a nominal activity of 100 mCi, low energy Germanium (LEGe) detector and 5 metal plates; they are Niobium (Nb), Molybdenum (Mo), Palladium (Pd), Silver (Ag) and Tin (Sn). The energy of the XRF emitted from those metal plates ranged from 16.59 keV– 25.26 keV. The experimental value of the mass attenuation coefficient of the particleboards and the calculated XCOM values for the middle-age breast group are comparable. However, there was no influence on the attenuation properties of the particleboard of PLA resin contents. Taken together, these results strongly suggest that bioplastic Rhizophora spp. particleboard has the potential of acting as a phantom material at diagnostic photon energy.